Elevated Levels of Serum Cholesterol are Associated with Better Performance on Tasks of Episodic Memory - Leritz, Elizabeth C. (Metab Brain Dis, 2016)
OBJECTIVE: We examined how serum cholesterol, an established risk factor for cerebrovascular disease (CVD), relates to cognitive function in healthy middle-older aged individuals with no neurologic or CVD history. METHOD: A complete lipid panel was obtained from a cohort of one hundred twenty individuals, ages 43–85, who also underwent a comprehensive neuropsychological examination. In order to reduce the number of variables and empirically identify broad cognitive domains, scores from neuropsychological tests were submitted into a factor analysis. This analysis revealed three explainable factors: Memory, Executive Function and Memory/Language. Three separate hierarchical multiple regression analyses were conducted using individual cholesterol metrics (total cholesterol, low density lipoprotein; LDL, high density lipoprotein; HDL, and triglycerides), as well as age, education, medication status (lipid lowering agents), ApoE status, and additional risk factors for CVD to predict neuropsychological function. RESULTS: The Memory Factor was predicted by a combination of age, LDL, and triglyceride levels; both age and triglycerides were negatively associated with factor score, while LDL levels revealed a positive relationship. Both the Executive and Memory/Language factor were only explained by education, whereby more years were associated with better performance. CONCLUSIONS: These results provide evidence that individual cholesterol lipoproteins and triglycerides may differentially impact cognitive function, over and above other common CVD risk factors and ApoE status. Our findings demonstrate the importance of consideration of vascular risk factors, such as cholesterol, in studies of cognitive aging.